Impact of Human Resource Competency Development on Employee Work Productivity - yartati, hermi (IKONOMIKA, 2021)
Manpower or employees are human resources who have a very important role in improving performance for the progress of a company. One of them is improving the performance of employees in Islamic banking companies that are known so far in sharia banking where development can be seen increasing. In this case, Islamic banking companies face challenges in employee work productivity, as a company in this case, namely sharia-related banking, which must have employees as human resources, namely employees who have competency development. Employees as human resources in question, namely employees as human resources who are also mentally and have a good attitude, and the assessment of knowledge from employees is a skill that must be more adequate.The formulation of the problem in an existing study is how the development of employee knowledge or competence as a human resource has an impact on the productivity of Bank employees from Syariah Indonesia KC Bengkulu S. Parman and the impact of how the development of employee competence is human resources in the field of Bank of Sharia Indonesia KC Bengkulu S. Parman. This study also has the aim of knowing whether there is an impact on developing an employee's competence as a human resource as well as on the productivity of Bank Syariah Indonesia employees at KC Bengkulu S. Parman. Basically the researcher uses a quantitative research approach. Sources of data that can be used are primary data. The primary data in this quantitative study are employees with a sample of 29 employees and the proportional method. The proportional method is in the form of validity and reliability tests. Descriptive data is in the form of perceptions of knowledge (XI), skills (X2), attitudes (X3), and productivity performance is (Y).In this study there are characteristics of some of the highest respondents who are seen from both male sex (79.3%), age 24-35 years (46.8%), S1 education (68.9%) and also working years >2 years (60.2%). Based on the results and discussion, the authors conclude that employees are human resources, who is one of the most important parts of the Bank Syariah Indonesia company KC Bengkulu S. Parman. Employees have competency development that must be good and also have a good basis of religious values and piety. Therefore, Bank Syariah Indonesia KC Bengkulu S. Parman will not easily be able to compete with other banks. Competency-based development that must be possessed is the basic characteristics of knowledge, skills, and attitudes related to productivity. The role of developing employee competencies as human resources at Bank Syariah Indonesia KC Bengkulu S. Parman has not looked so good because employees have not fully developed good competencies. This will have an impact on the productivity of employees.Keywords: Development of competence, human resources, employee productivity, Bank Syariah Indonesia KC Bengkulu S. Parman.